Insomnia Related with Intellectual Function in the Elderly - Wahidyanti Rahayu Hastutiningtyas; Nurul Aisyiyah Puspitarini (Journal Of Nursing Practice, 2026)
Background: Insomnia is a common sleep disorder among older adults that can negatively affect quality of life and intellectual function. Impaired intellectual function may reduce independence, limit daily activities, and hinder social interactions. Purpose: This study aimed to determine the relationship between insomnia and intellectual function among older adults attending the Elderly School in Bandungrejosari, Malang City. Methods: This quantitative correlational study involved 30 older adults selected through simple random sampling. Insomnia was assessed using the KSBPJ-IRS questionnaire, while intellectual function was measured using the Short Portable Mental Status Questionnaire (SPMSQ). Data were analyzed using a correlation test to examine the relationship between insomnia and intellectual function. Results: A significant relationship was found between insomnia and intellectual function (p = 0.002). Higher levels of insomnia were associated with lower intellectual function, indicating that sleep disturbances may contribute to cognitive decline in older adults. Conclusion: Insomnia was significantly associated with intellectual function among older adults at the Elderly School in Bandungrejosari, Malang City. Improving sleep quality may help preserve intellectual function and enhance the quality of life of older adults.